2018
DOI: 10.4236/ojo.2018.83011
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcomes after Triceps Splitting versus Triceps Sparing Approach for Extra-Articular Distal Humerus Fractures

Abstract: Aim: To compare the functional outcome as well as elbow range of motion (ROM) after triceps splitting and triceps sparing approach for AO/OTA TYPE A distal humerus fractures. Materials and Methods: This is a prospective study done at our center between 2011 and 2014. A total of 50 patients presented with extra articular distal humerus fracture (AO/OTA 13 A2, 13A3). Exclusion criteria removed 16 patients from the study while 2 patients died due to medical comorbidities before the final follow up. Out of the rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Jagdeep et al [3] reported that, the mean time of bone union was 11.8 ± 2.8 in triceps splitting, and 12.0 ±3.6 months in triceps sparing with non-significant difference. The mean elbow flexion was 140.0 ± 4.0 and 126.0±10.0 in triceps sparing and triceps splitting groups respectively, with significant difference.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Jagdeep et al [3] reported that, the mean time of bone union was 11.8 ± 2.8 in triceps splitting, and 12.0 ±3.6 months in triceps sparing with non-significant difference. The mean elbow flexion was 140.0 ± 4.0 and 126.0±10.0 in triceps sparing and triceps splitting groups respectively, with significant difference.…”
Section: Discussionmentioning
confidence: 98%
“…Illica et al [11] reported that, the mean DASH score was [14.45 ± 12.17] in triceps sparing. Jagdeep et al [3] reported that, the mean DASH score was [24.28 ± 10.14] in triceps sparing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations